Optimal BMI Grouping and Timing Selection Based on NIPT Test Data - Wang, Shuhan; Sun, Wenqi; Lin, Chunyu (International Journal of Public Health and Medical Research, 2026)
To further enhance the accuracy of non-invasive prenatal testing (NIPT) technology, this study analysed the correlation between NIPT results and factors such as gestational age and maternal body mass index (BMI), based on real-world data from 1,082 male fetuses and 605 female fetuses in China. First, Spearman's correlation coefficient analysis was conducted, revealing strong correlations between Y chromosome concentration and gestational age, BMI, and X chromosome concentration. Subsequently, K-means clustering revealed a distribution relationship between the optimal NIPT testing time point and different BMI intervals among pregnant women carrying male fetuses. Furthermore, a comprehensive BMI grouping model was developed by integrating multivariate clustering with optimization of the mean Y chromosome concentration. Constrained by a post-clustering Y-chromosome concentration mean exceeding 0.65% within each group and inter-group mean differences below 0.1%, the comprehensive BMI grouping results were: (20.70, 30.21], (30.21, 31.81], (31.81, 33.93], and (33.93, 46.88]. The corresponding optimal NIPT timepoints were 12.14, 13.28, 14.35, and 14.60 weeks respectively.